THE EFFECT OF USING THE MASTERY AND COOPERATIVE METHODS IN LEARNING THE SKILL OF SHOOTING FROM A STANDSTILL IN BASKETBALL (American Journal of Pedagogical and Educational Research, 2023)
The characteristic of the era in which we live is characterized by rapid change and renewal in accordance with the additions to knowledge and changes to the social structure. Sport, with its characteristics, has become a national necessity in building the country and giving confidence in its future. Therefore, we must choose ideas that are tested over time and when applied produce results. A high-level achievement. There are tried and tested strategies to improve and enrich the sporting reality and to acquire and understand all the new sports sciences related to sports performance. Basketball is one of the team games in which the success of any team depends mainly on the extent of its members’ proficiency in the basic skills of the game. One of the skills of great importance in the game of basketball is shooting, as victory in this game depends on the team that earns the largest number of points. Shooting is considered one of the offensive and decisive skills, as through it it is possible to obtain a direct point, and this skill in motor learning is considered one of the only movement skills, so the researcher decided to learn this type of shooting, through the use of the mastery and cooperative methods. The research problem lies in conducting a serious scientific study of this problem through the use of the mastery and cooperative methods within the educational curriculum approved by the college. The study aimed to identify the effect of the mastery and cooperative learning styles on learning the skill of shooting from a standstill in basketball. The researcher assumed that the mastery learning method is better for learning the skill of shooting than holding a basketball. The researcher used the experimental method to suit the research problem, and the research sample was randomly selected from second-year students.Through the results, the researcher reached the following conclusions:.1 Using the mastery method in learning has a very large and effective impact on learning the skill of shooting from a standstill in basketball.